The Case for a Construction Industry Council in Ghana - Kuragu, Joseph Kwame Ofori; Manu , De Graft Owusu; Ayarkwa, Joshua (Penerbit Universiti Sains Malaysia, 2016)
The Ghanaian construction industry faces major problems that undermine its potential and contribution to overall national development. There is a general acceptance of the need to develop structures and improve regulations within the Ghanaian construction industry. However, the fragmentation of stakeholders has resulted in the absence of a clear agenda within the industry to address apparent problems that affect performance within the industry. Whilst there have been previous initiatives to help deliver industry-wide improvements in the Ghanaian construction industry, they have not received direct sustained attention from a single organisation with broad stakeholder participation. This undermines progress in the efforts to improve the overall environment and performance in the industry. This paper explores the development of a multi-stakeholder representative body for the Ghanaian construction industry to provide leadership in the pursuit of reform in the Ghanaian construction industry. The literature on developments within the global construction industry and industry initiatives to improve performance have been reviewed. This provides new pathways to ongoing efforts to achieve industry-wide regulation. It has been recognised in this paper that the ultimate objective towards the attainment of industrywide improvements in the Ghanaian construction industry remains the establishment of an Industry Development Agency